Production of sugars from sago bark using subcritical water treatment - M. Amin, Nurhusni (2019)
Sago bark is one of the solid wastes being discarded in large volume from sago industries and currently being abandoned and underutilized. The effort to valorize this waste is not enlarge due to the technology limitation. Besides, the current practices on the sago wastes left at the sago starch processing industries have raised to various environmental issues. Due to its large in carbon content, sago bark is subjected to subcritical water treatment in this study for producing sugars and other value-added products. Sago bark was differentiated into inner and outer layers and both were treated at 180 - 320 °C for 5 min. It was found that inner layer yielded higher amount of TOC (0.27 g/g-dry sago bark) and total sugar (0.67 g/g-dry sago bark) than the outer layer at 210 °C. Inner layer was also substantially affected with more than 90% solid loss recorded with increasing reaction temperature and maximum tar yield of 0.41 g/g-dry sago bark at T≥280 °C. Besides, inner layer had shown better conversion and solubility in subcritical water thus, it is more susceptible to subcritical water treatment than the outer layer. Inner layer was selected for further experiments under varied reaction times, 1 - 15 min. Temperatures of 180, 210 and 240 °C were selected and made constant at a time. Temperature of 210 °C and reaction time 5 min yielded the highest total sugar yield among the other reaction temperatures. The production of tar was less affected by the prolonged reaction time unlike at higher temperature. It was noticed that polysaccharide in the bark decomposed sequentially from higher to lower degree of polymerization. Hemicellulose decomposed earlier (180 °C, 5 min) than the cellulose portion (≥210 °C, ≥7 min). Among all of reaction temperatures applied, 240 °C showed better monosaccharides yields (glucose = 0.093, xylose = 0.097 g/g-dry sago bark) in shorter time, 5 min. 210 °C was a suitable temperature for arabinose production with the highest yield of 0.015 g/g-dry sago bark at 2 min. The drop of pH combined with increase amount of organic acids generated confirmed that, sugars degradation had happened at higher reaction temperature and time. The six types of organic acid identified were pyruvic, malic, acetic, formic, succinic and lactic acids. The declining thermogravimetric analysis combustion values, from 80 to 60 wt. % for the reaction temperature 180 - 240 °C further supported that sago bark had successfully decomposed during the reaction. The thermogravimetric analysis also revealed that hemicellulose decomposed the most during the reaction rather than the cellulose and resulted in large contribution to the sugar yields. The increasing crystallinity index obtained, 59.3 - 78.1% when treated at 180 - 240 °C as compared to the raw sago bark, 38.6%, further verified the efficient removal of certain amount of lignin and hemicellulose from the solid sample matrix. The crystallinity index became evident that only amorphous region of cellulose was affected thus, contributed into the cellulose sugars production i.e. glucose at higher temperature and time.